2014
DOI: 10.1177/0042098014523687
|View full text |Cite
|
Sign up to set email alerts
|

Foreign liquidity to real estate market: Ripple effect and housing price dynamics

Abstract: Globalisation enables foreign liquidity to access local property markets. This paper depicts a strong connection between foreigners’ property acquisitions and regional housing price movements in Singapore. Testing structure breaks also illustrates a ripple effect of prices from the central city to suburbs. A structural vector autoregression incorporates these two observations. Impulse-response function and forecast-error variance decomposition show that central region’s foreign-liquidity shocks can greatly imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 38 publications
0
24
0
1
Order By: Relevance
“…Property investors often prefer apartments because maintenance responsibilities and costs are comparatively low, and they can buy into good locations more cheaply than for detached, stand-alone housing (Altmann, 2014). The central importance of condominium properties to the global flow of investment capital in and between cities such as New York, Hong Kong, London, Vancouver and Sydney is well documented, as are the implications for house prices in these cities and the ability of local residents to purchase apartments in which to live (Liao et al, 2015;Surowieki, 2014). However, in many cities, local domestic investors have an even greater impact on the housing market, not only in terms of the price of properties, but also their design and quality (Sharam et al, 2015).…”
Section: The Politics and Practices Of Apartment Livingmentioning
confidence: 99%
“…Property investors often prefer apartments because maintenance responsibilities and costs are comparatively low, and they can buy into good locations more cheaply than for detached, stand-alone housing (Altmann, 2014). The central importance of condominium properties to the global flow of investment capital in and between cities such as New York, Hong Kong, London, Vancouver and Sydney is well documented, as are the implications for house prices in these cities and the ability of local residents to purchase apartments in which to live (Liao et al, 2015;Surowieki, 2014). However, in many cities, local domestic investors have an even greater impact on the housing market, not only in terms of the price of properties, but also their design and quality (Sharam et al, 2015).…”
Section: The Politics and Practices Of Apartment Livingmentioning
confidence: 99%
“…Employing a panel database of quarterly real housing prices for 22 advanced and 31 emerging economies from 2000Q1 to 2014Q4, Jara and Romero (2016) also found that banking integration positively and significantly affects the synchronicity of housing prices. The third strand of literature analyzes housing price synchronization from liquidity or capital perspective (Longstaff 2010;Hoesli and Reka 2015;Cesa-Bianchi et al 2015;Eickmeier and Ng 2015;Liao et al 2015;Hau and Lai 2017). Employing daily data from the ABX Indices of collateralised-debt obligations (CDOs) from January 19, 2006to December 31, 2008, Longstaff (2010 found that the return volatility of subprime CDOs is able to predict the return volatility of stocks and bonds 3 weeks before, which is propagated via liquidity and risk-premium channels rather than by correlated-information channels.…”
Section: Introductionmentioning
confidence: 99%
“…Real estate has remained a topic of research interest since the 1980s, but most has focused on the issue of why investors chose to own real estate and the potential benefits of the diversifying real estate (Liao, Zhao, Lim, Wong, & Wong, 2015). One group of the researchers has focused on portfolio analysis of real estate (e.g., Case, Goetzmann, & Rouwenhorst, 2000;Eichholtz, Hoesli, MacGregor, & Nanthakumaran, 1995), while another has focused on both real estate and financial assets (e.g., Graeme & James, 1996;Hoesli, Lekander, & Witkiewicz, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an increasing trend of foreign liquidity in local real estate has been observed (Bardhan & Kroll, 2007). According KEYWORDS house Prices; stock Prices; Dynamic oLs; EU countries to the statistics of 2009, ~ 10% of the real estate sales were generated from foreigners, while this figure was 35% in the Asian Pacific region (Liao et al, 2015). These statistics identify that foreigners are a cure for the bearish real estate market.…”
Section: Introductionmentioning
confidence: 99%